CLIMATE CHANGE AND AGRICULTURAL PRODUCTION IN THE GAMBIA: AN ARDL ANALYSIS OF FOOD SECURITY CHALLENGES - manneh, Bakary; Darboe, Fatou (OECONOMICUS Journal of Economics, 2025)
This paper empirically investigates the impact of climate change on agricultural production and food security in The Gambia from 1990 to 2020. Using annual time-series data, the study applies Augmented Dickey–Fuller (ADF), Phillips–Perron (PP) tests, and the Autoregressive Distributed Lag (ARDL) model to examine short and long-term relationships between the Food Production Index (FPI), cereal yield, land under cereal production, agricultural land, carbon dioxide (CO₂) emissions, greenhouse gas (GHG) emissions, and population growth. Results indicate that cereal yield, agricultural land, and land under cereal production positively influence FPI, while GHG emissions exert a significant negative effect in both the short and long run. CO₂ emissions show a mixed impact depending on time horizon. These findings corroborate earlier studies in West Africa yet fill a research gap by offering a time-series econometric assessment focused exclusively on The Gambia. The study highlights the importance of integrating climate adaptation and mitigation policies with agricultural development strategies to enhance national food security. Policy recommendations include strengthening climate-resilient crop research, implementing low-emission farming practices, and institutionalizing farmer training on climate adaptation. The article contributes to the growing literature on climate change and food security in Sub-Saharan Africa by linking statistical modeling with policy-relevant insights.